Integrative and complementary practices from the perspective of primary care health professionals (Research, Society and Development, 2022)
The Policy on Integrative and Complementary Practices was instituted in 2006 in the Unified Health System, but it is still not widespread. With the inclusion of more practices in 2017 and 2018, this theme became more evident. This study aims to describe the knowledge of health professionals about Integrative and Complementary Practices in Primary Care, identifying the most used and pointing out the challenges presented for their implementation. This is an integrative review study. The data source used was the VHL (Virtual Health Library) and Google academic, using the descriptors: “Integrative and complementary practices”, “Primary Care” and “Public Health”. A total of 3,262 articles were found, but only 11 were selected for the study based on the inclusion criteria used. The results showed a lack of knowledge on the part of professionals about the Policy on Integrative and Complementary Practices, however, in the places where the practices were carried out, many benefits were noticed, both for professionals and for users. Thus, this study points to the need to sensitize health professionals and students about the importance and effectiveness of using these practices in the teaching and learning process in Basic Health Units.